2018
DOI: 10.1186/s12864-018-5222-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis revealed rapid differentiation in the pathogenicity-related gene repertoires between Pyricularia oryzae and Pyricularia penniseti isolated from a Pennisetum grass

Abstract: BackgroundA number of Pyricularia species are known to infect different grass species. In the case of Pyricularia oryzae (syn. Magnaporthe oryzae), distinct populations are known to be adapted to a wide variety of grass hosts, including rice, wheat and many other grasses. The genome sizes of Pyricularia species are typical for filamentous ascomycete fungi [~ 40 Mbp for P. oryzae, and ~ 45 Mbp for P. grisea]. Genome plasticity, mediated in part by deletions promoted by recombination between repetitive elements … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…[157] and Neurospora crassa [158] were among the identified Sordariomycetes and they convert cellulose into ethanol. Magnaporthales such as Pyricularia penniseti convert isoamylalcohol into isovaleraldehyde while other Magnaporthales' species convert fumaryl-acetoacetate into fumarate and acetoacetate [159,160]. Other roles played by the Sordariomycetes' species include the metabolism of aromatic compounds through which, phenolics and aryl alcohols/aldehydes are converted into acetate, formate and ethanol [161,162].…”
Section: The Identified Fungal Biomesmentioning
confidence: 99%
“…[157] and Neurospora crassa [158] were among the identified Sordariomycetes and they convert cellulose into ethanol. Magnaporthales such as Pyricularia penniseti convert isoamylalcohol into isovaleraldehyde while other Magnaporthales' species convert fumaryl-acetoacetate into fumarate and acetoacetate [159,160]. Other roles played by the Sordariomycetes' species include the metabolism of aromatic compounds through which, phenolics and aryl alcohols/aldehydes are converted into acetate, formate and ethanol [161,162].…”
Section: The Identified Fungal Biomesmentioning
confidence: 99%
“…The filamentous fungus M. oryzae is the causal pathogen of rice blast disease, which leads to substantial losses in rice production annually (15,30). Our previous studies suggested that the host plant is the major force that shapes the M. oryzae genome (20,21,31). However, no real-time assays have been performed so far to investigate the occurrence and accumulation of mutations in M. oryzae populations in interaction with rice plants.…”
Section: Discussionmentioning
confidence: 99%
“…Many events have been driving the gain or loss of related-virulence and avirulence genes involved in pathogenicity. For example, mixed infections in shared hosts favors gene flow through sexual recombination or non-meiotic parasexual processes, (Talbot et al 1993a, b;Soanes et al 2002;Inoue et al 2017;Monsur and Kusaba 2018;Zheng et al 2018;Gómez Luciano et al 2019;Asuke et al 2019), mutations in avirulence genes through selecting frequently occurs (Orbach et al 2000), or through the moving of a Pot3 transposon across pathogenicity related-genes (Kang et al 2001). Pathogenic effector proteins have been under evolutive selection across blast populations (Sweigard et al 1995;Farman and Leong 1998;Jones and Dangl 2006;Avila-Adame 2014;Tosa et al 2016;Wang and Valent 2017;Inoue et al 2017Inoue et al , 2021Gladieux et al 2018;Langner et al 2018;Gómez Luciano et al 2019), which might explain the ability to infect a new host or the variable levels of aggressiveness across different hosts (Kato et al 2000;Tosa et al 2004;Castroagudín et al 2016;Perelló et al 2017;Urashima et al 2017;Reges et al 2018Reges et al , 2019Qi et al 2021).…”
Section: Taxonomy and Genetic Diversitymentioning
confidence: 99%